Avoidance of lower limb amputation from a diabetic foot ulcer: The importance of multidisciplinary practice and patient collaboration - Margaret Mungai and Emmy Sirmah (WCET Journal - Spanish Edition, 2019)
This article explores wound care nursing interventions and inter-professional collaboration for a patient referred with a stage 3 diabetic foot ulcer (DFU). To the patient’s distress, he had been informed that he may require an amputation due to the severity of his DFUs. On initial presentation, the patient was symptomatic for peripheral neuropathy, infection and hyperglycaemia. The left lower limb was oedematous and there was a DFU at the metatarso-phalangeal joint of the big toe on his left foot secondary to haemorrhagic callus. Progressive healing of the DFU was realised over time by repetitive debridement; incision and drainage of the DFUs; antibiotic therapy; appropriate footwear; dietary instructions; control of the blood sugar levels (BSLs); and patient and family education. Wound care nursing interventions were applied in conjunction with medical management of the DFUs. The DFUs were managed using a locally made, two-part zinc oxide gauze dressing known as the Unna boot. A family member was instructed how to continue applying the dressings at home in between clinic visits. Complete wound healing was eventually achieved within four months, thus avoiding the need for amputation.